Integrin beta 1 cytoplasmic domain dominant negative effects revealed by lysophosphatidic acid treatment. - Smilenov, L (1994)
Integrin receptors localize to focal contact sites and interact with the cytoskeleton via the beta 1 cytoplasmic domain. To study the role of this domain in adhesion, we have expressed in NIH 3T3 cells a cDNA consisting of the interleukin 2 receptor alpha subunit extracellular and transmembrane domains, connected to the integrin beta 1 cytoplasmic domain (IL2R-beta 1). Since the extracellular domain of the chimeric protein has no role in adhesion, this protein could uncouple adhesion from intracellular events. As expected, in a cell line expressing IL2R-beta 1, this chimera was directed to focal contact sites. Unexpectedly, the cells exhibited normal adhesion to fibronectin (FN). However, when a rapid reorganization of the cytoskeleton was induced using lysophosphatidic acid (LPA), IL2R-beta 1 cells detached from FN in contrast to wild-type cells. The detachment in response to LPA could be prevented with cytochalasin D, an inhibitor of actin polymerization. These results imply that a beta 1 cytoplasmic domain, which is uncoupled from adhesion, can compete with the cytoplasmic domain of native integrin beta 1 for cytoskeletal proteins. As a consequence, the IL2R-beta 1 protein acts as a dominant negative effector of adhesion by disrupting the integrin-cytoskeleton connection.